Cyclic photochemical re-growth of gold nanoparticles: Overcoming the mask-erosion limit during reactive ion etching on the nanoscale - Özdemir, Burcin; Seidenstücker, Axel; Plettl, Alfred; Ziemann, Paul (Beilstein Journal of Nanotechnology, 2013)
The basic idea of using hexagonally ordered arrays of Au nanoparticles (NP) on top of a given substrate as a mask for the subsequent anisotropic etching in order to fabricate correspondingly ordered arrays of nanopillars meets two serious obstacles: The position of the NP may change during the etching process and, thus, the primary pattern of the mask deteriorates or is completely lost. Furthermore, the NP are significantly eroded during etching and, consequently, the achievable pillar height is strongly restricted. The present work presents approaches on how to get around both problems. For this purpose, arrays of Au NPs (starting diameter 12 nm) are deposited on top of silica substrates by applying diblock copolymer micelle nanolithography (BCML). It is demonstrated that evaporated octadecyltrimethoxysilane (OTMS) layers act as stabilizer on the NP position, which allows for an increase of their size up to 50 nm by an electroless photochemical process. In this way, ordered arrays of silica nanopillars are obtained with maximum heights of 270 nm and aspect ratios of 5:1. Alternatively, the NP position can be fixed by a short etching step with negligible mask erosion followed by cycles of growing and reactive ion etching (RIE). In that case, each cycle is started by photochemically re-growing the Au NP mask and thereby completely compensating for the erosion due to the previous cycle. As a result of this mask repair method, arrays of silica nanopillar with heights up to 680 nm and aspect ratios of 10:1 are fabricated. Based on the given recipes, the approach can be applied to a variety of materials like silicon, silicon oxide, and silicon nitride.
Keywords: Au nanoparticles; block copolymer micellar lithography; photochemical growth; reactive ion etching; self-assembly

(untitled) - Manzke, A.; Vogel, N.; Weiss, C. K.; Ziener, U.; Plettl, A.; Landfester, K.; Ziemann, P. (Nanoscale, 2011)

(untitled) - Manzke, A.; Plettl, A.; Wiedwald, U.; Han, L.; Ziemann, P.; Schreiber, E.; Ziener, U.; Vogel, N.; Weiss, C. K.; Landfester, K.; Fauth, K.; Biskupek, J.; et al. (Chem. Mater., 2012)

(untitled) - Krishnamoorthy, S.; Pugin, R.; Hinderling, C.; Brugger, J.; Heinzelmann, H. (Nanotechnology, 2008)

(untitled) - Aydin, D.; Schwieder, M.; Louban, I.; Knoppe, S.; Ulmer, J.; Haas, T. L.; Walczak, H.; Spatz, J. P. (Small, 2009)

(untitled) - Kästle, G.; Boyen, H.-G.; Weigl, F.; Lengl, G.; Herzog, T.; Ziemann, P.; Riethmüller, S.; Mayer, O.; Hartmann, C.; Spatz, J. P.; Möller, M.; Ozawa, M.; et al. (Adv. Funct. Mater., 2003)

(untitled) - Wiedwald, U.; Han, L.; Biskupek, J.; Kaiser, U.; Ziemann, P. (Beilstein J. Nanotechnol., 2010)

(untitled) - Bansmann, J.; Kielbassa, S.; Hoster, H.; Weigl, F.; Boyen, H.-G.; Wiedwald, U.; Ziemann, P.; Behm, R. J. (Langmuir, 2007)

(untitled) - Enderle, F.; Dubbers, O.; Plettl, A.; Ziemann, P. (Beilstein J. Nanotechnol., 2012)

(untitled) - Morton, K. J.; Nieberg, G.; Bai, S.; Chou, S. Y. (Nanotechnology, 2008)

(untitled) - Krishnamoorthy, S.; Gerbig, Y.; Hilbert, C.; Pugin, R.; Hinderling, C.; Brugger, J.; Heinzelmann, H. (Nanotechnology, 2008)

(untitled) - Park, H. J.; Kang, M.-G.; Guo, L. J. (ACS Nano, 2009)

(untitled) - Ghoshal, T.; Senthamaraikannan, R.; Shaw, M. T.; Holmes, J. D.; Morris, M. A. (Nanoscale, 2012)

(untitled) - Brown, K. R.; Natan, M. J. (Langmuir, 1998)

(untitled) - Brown, K. R.; Walter, D. G.; Natan, M. J. (Chem. Mater., 2000)

(untitled) - Härtling, T.; Seidenstücker, A.; Olk, P.; Plettl, A.; Ziemann, P.; Eng, L. M. (Nanotechnology, 2010)

(untitled) - Mallick, K.; Wang, Z. L.; Pal, T. (J. Photochem. Photobiol., A: Chem., 2001)

(untitled) - Lohmueller, T.; Bock, E.; Spatz, J. P. (Adv. Mater., 2008)

(untitled) - Liu, P.; Ding, J. (Langmuir, 2010)

(untitled) - Purwaningsih, L.; Schoen, T.; Wolfram, T.; Pacholski, C.; Spatz, J. P. (Beilstein J. Nanotechnol., 2011)

(untitled) - Wood, M. A.; Riehle, M.; Wilkinson, C. D. W. (Nanotechnology, 2002)